Kant’s anti-colonialism based on the limited scope of the individual right to hospitality - Giesen, Klaus-Gerd (Monitor ISH, 2023)
Kant’s position on the colonial question has mostly been discussed by referring to his conceptions of relationships between collective groupings (states, nations, ‘races’, peoples). The text argues that his strong anti-colonial stance rather stems from his normative framework – developed in the second half of the 1790s – of a limited scope of the right to hospitality that an individual is intitled to enjoy upon arrival on a foreign territory.
Keywords: anti-colonialism; antikolonializem; colonialism; cosmopolitanism; človekove pravice; ethics; etika; Kant, Immanuel; kolonializem; kozmopolitizem